RANCANG BANGUN SCORING BOARD MENGGUNAKAN SMS (SHORT MESSAGE SERVICE) BERBASIS MIKROKONTROLER ATMEGA 32 - ., Zeky Leo Karza (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstrack: Scoring Board via SMS is a microcontroller-based system that can be used to provide information about the results of football matches, both scor match results and team names that match. To input the name of the team in the scoring system board must send a sms with a given format ie